Bioethics, principles and ethical dilemmas in dentistry - Suárez-Ponce, Daniel (2016)
Bioethics arises from the need to respond and try to solve the major conflicts that arise in society. Bioethics is a modern term that is attributed paternity Van Rensselaer Potter (1970) by publishing the article “Bioethics, the science of survival,” Potter establishes the existence of a close relationship between the world of life sciences, his deeds and ethical values, bioethics subsequently primarily it related to medical ethics. Tom L. Beauchamp and James F. Childress published “Principles of biomedical ethics” 1979, being considered a classic text in biomedical ethics, in which four bioethical principles states: autonomy, non-maleficence, beneficence and justice. Analysis and bioethical reflection are essential in the practice of the dentist, this will allow a clinical practice based on values, which would involve all health personnel, guiding strategies to address adequately the ethical dilemmas that may arise during the patient care process. Finally dental practice requires a higher professional level values.